STRATEGIC INVESTMENT DIRECTIONS IN LOGISTICS SYSTEMS OF CORPORATIONS - Makhmudov Samariddin Bakhriddinovich (Innovate Conferences, 2025)
This article assesses the strategic investment directions of corporate structures in the logistics system. The development of logistics infrastructure, modernization of transport vehicles, construction of warehouses and distribution centers, as well as investments in digital technologies are indicated as the main factors for increasing competitiveness in international markets. The role of foreign market entry, licensing and operating costs in the structure of investment costs is also highlighted. According to the results of the study, the comprehensive and phased implementation of investments is reflected in ensuring the efficiency of logistics systems, optimizing costs, and long-term sustainable development of corporations
Keywords: Strategic investments, corporate logistics, logistics systems, infrastructure development, transport modernization, supply chain management, financial optimization